Design and Implementation of Large Computer Room Environment Intelligent Monitoring System Based on Zigbee - Li, Jin Qiang; Sun, Ling; Zhao, Xing Chen; Shi, Quan; Liu, Jian (Applied Mechanics and Materials, 2013)
For large network communication equipment are in need of real time computer maintenance and management, the traditional manual management can't meet this need, so this paper designs a set of real-time data acquisition, intelligent alarm and remote control, large computer room environment monitoring system based on Zigbee. The system is composed of terminal monitoring subsystem, control subsystem and management terminal. The terminal monitoring system consists of ZigBee node through the network, and its data acquisition include temperature, humidity and smoke environmental data; MSP430F1611 and Ethernet module monitoring subsystem are responsible for packet analysis, Ethernet connection, and Web intelligent remote switch control when monitoring data reaches a threshold. The system also can be used in street lamp remote intelligent control, intelligent irrigation control system of greenhouse vegetables and so on. Therefore, it has good application value.